Cone-beam computed tomographic analysis: Comparison of the efficacy of two rotary retreatment systems for removal of filling material from primary teeth obturated with contemporary endodontic sealers - Moreira, Camila Said; Martinho, Frederico Canato; Coelho, Marcella Pavanello Batista; Coutinho Júnior, Luis Roberto Manhães; da Silva, Eduardo Galera; Torres, Carlos Rocha Gomes; Gomes, Ana Paula Martins (Jaypee Brothers Medical Publishing, 2015)
Introduction: This study has used cone-beam computed tomography (CBCT) to evaluate the efficacy of two different nickel titanium (NiTi) rotary retreatment systems for removal of filling material from teeth obturated with contemporary endodontic sealers. The operative time required for removal of root filling materials was also evaluated. Methods: Sixty root canals were randomly divided into three groups according to the sealer used for obturation: AH Plus Jet, mineral trioxide aggregate (MTA) Fillapex, and RoekoSeal Automix (RSA) (all, n = 20). After obturation, each group was subdivided into two subgroups according to the NiTi retreatment rotary system: Mtwo retreatment (Mtwo-R) file subgroup and ProTaper-UR subgroup–both instrumented with Mtwo-R files. Teeth were scanned with a microcomputed tomography before and after obturation. Results: Residual filling material was observed in 100% of the specimens after retreatment. No difference was found between Mtwo-R and ProTaper-UR systems (p > 0.05). The RSA was more effectively removed from dentin walls than AH Plus Jet (p < 0.05), with no difference to MTA Fillapex (p > 0.05). Thus, teeth obturated with RSA required less operative time to be retreated (both, p<0.05). Conclusion: ProTaper-UR and Mtwo-R systems were effective in removing the filling materials after instrumentation, but they could not eliminate them completely. Moreover, teeth obturated with silicone-based sealer RSA showed less residual filling material in dentin walls compared to the epoxy resin-based sealer (AH Plus Jet), which exhibited no difference compared to the salicylate resin-based sealer (MTA Fillapex). Teeth obturated with silicon-based sealer also required less operative time to be retreated despite the NiTi rotary retreatment system tested.
Keywords: NiTi retreatment system; Retreatment; Root canal; Sealer